2018
DOI: 10.1111/ecoj.12585
|View full text |Cite
|
Sign up to set email alerts
|

Self-selection of Emigrants: Theory and Evidence on Stochastic Dominance in Observable and Unobservable Characteristics

Abstract: The Roy model has more precise predictions about the self-selection of migrants than previously realised. The conditions shown to result in positive or negative selection in terms of expected earnings also imply a stochastic dominance relationship between the earnings distributions of migrants and non-migrants. We test these predictions using the Danish full population administrative data. We find strong evidence of positive self-selection of emigrants in terms of pre-emigration earnings and residual earnings:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 46 publications
2
53
1
Order By: Relevance
“…Particularly valuable is my focus on a country not yet studied but which experienced high emigration rates over the period analysed. Differently from Borjas et al (2019) who focus on emigration from a rich EU country (Denmark), Poland is to be considered the largest emerging country within the European context. Before the 2004 accession, average monthly earnings were 4 times lower in Poland than the average in the EU15 countries 2 and, typical of transition economies, the country experienced large fluctuations in the unemployment rate, from 10 percent in 1998 to 19 percent in 2004, and back to 7 percent in 2008.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly valuable is my focus on a country not yet studied but which experienced high emigration rates over the period analysed. Differently from Borjas et al (2019) who focus on emigration from a rich EU country (Denmark), Poland is to be considered the largest emerging country within the European context. Before the 2004 accession, average monthly earnings were 4 times lower in Poland than the average in the EU15 countries 2 and, typical of transition economies, the country experienced large fluctuations in the unemployment rate, from 10 percent in 1998 to 19 percent in 2004, and back to 7 percent in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…I implement the empirical analysis of Gould and Moav (2016) for this case and extend it to the comparison of two destination countries, reviewing the role of migration policies as possible drivers of the observed outcomes. As argued by Borjas et al (2019) there is a need for further evidence to improve the understanding of the role of residual wage inequality in determining emigrant selection. The literature has so far pointed out the importance of focusing not only on observable skills but also on unobservable skills, allowing for the possibility that individuals with identical education levels have different levels of unobservable skills (Gould and Moav 2016;Borjas et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Borjas et al. () found that more than half of the difference between the expected earnings of migrants and non‐migrants arises because of differences in unobserved characteristics. The above studies on self‐selection concentrate on migration from a developing country to a developed country.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Since Borjas (1987) formalized the Roy model (Roy 1951), migrant selection has become a prolific topic in labour economics, because it provides a framework to study migrant 'quality' in contemporary and past migration episodes (Abramitzky et al 2012;Borjas et al 2018;Chiquiar and Hanson 2005;Kosack and Ward 2014;Spitzer and Zimran 2018;among others). While the literature on migrant self-selection acknowledges that the decision to migrate depends on systemic and idiosyncratic reasons, the factors that may explain shifts in selection patterns over time remain empirically unexplored (Abramitzky and Boustan 2017: 1325).…”
Section: Introductionmentioning
confidence: 99%